Anticancer properties of beta-caryophyllene and d-limonene terpenes: A review - Ololade S. Gbadebo; Elizabeth D. Oke; Felix A. Ajibuwa (Asian Pacific Journal of Tropical Biomedicine)
Terpenes are a structurally diverse family of secondary metabolites found mostly in plants and microorganisms. Beta-caryophyllene and d-limonene are abundant in aromatic medicinal plants. Beta- caryophyllene can be sourced from clove and cannabis amongst others, and d-limonene is abundant in the Citrus genera. Apart from their use in agriculture, cosmetics, and food industries, these terpenes possess a wide range of therapeutic activities, including antimicrobial, analgesic, and anticancer activities. This review discusses the anticancer effects of these two compounds against malignant tumors including breast, lung, gastrointestinal, bone, blood, endometrial, and bladder cancer. Beta-caryophyllene induces apoptosis and prevents proliferation and metastasis through the downregulation of HSP60, HTRA, survivin, XIAP, Bcl-xL, and Bcl-2 and the upregulation of caspase 3, annexin V, p21, Bad, Bak, and Bax. The anticancer activity is also mediated by G1/M arrest, ROS induction, and JAK1/STAT activation. d-Limonene exerts its anticancer effects by upregulating autophagy-linked genes, Bax, and caspase 3 and downregulating cyclin D1 and Bcl-2. These compounds also elicit synergistic effects upon co-administration with anticancer drugs and show great prospects as useful agents in the fight against cancer.